Determinants of Successful Implementation of Early Childhood Development Education by County Governments in Kenya; Implementing Partners Perspective (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the determinants of successful implementation of Early Childhood Development Education (ECDE) by County Governments in Kenya from the implementing partners’ perspective. This study was guided by the following specific objectives: to determine the influence of the capacities of the County Government staff on the implementation of early childhood development education by County Governments in Kenya, to determine the how management of early childhood development education affects its implementation by County Governments in Kenya, to assess how availability of physical facilities affect the implementation of early childhood development education by County Governments in Kenya and to examine how policies affect the implementation of early childhood development education by County Governments in Kenya. Decentralization theory and organization learning theory were used to explain the relationship between the study variables. Descriptive research design was used in the study. The population for the study was implementing partners working with County Governments in Kenya to support ECDE. Purposive sampling technique was used to select the respondents to participate in the study. A total of 100 respondents were targeted from the 10 organizations studied out of which 70 participated giving a response rate of 70%. Questionnaire was used as instrument for data collection. Both qualitative and quantitative data analysis techniques were used to analyze the data. The study found that the implementation of ECDE by County governments in Kenya was generally successful from the implementing partners’ perspective and indicated by 56.8%. It is also worth noting that beside the general success, there were myriads of challenges facing the implementation of the program by county governments. Findings from regression analysis showed that the coefficient of determination indicated that 63.5% of the variations on the implementation of ECDE by county governments can be explained by staff capacity, management of ECDE, availability of physical facilities and ECDE policies. The remaining 36.5% can be explained by other variables not included in the study. R square and adjusted R is above average an implication that an above average variation can be explained by the model. The study recommended that county governments should allocate more funds for the renovation and construction of more ECDE centres, allocate adequate funds for the implementation of ECDE and that they should organize consistent in-service training for ECDE teachers and at the same time employ more ECDE staff to cater for the large number of children in ECDE centres..